Analisis Penerapan Isak 35 Tentang Penyajian Laporan Keuangan Entitas Berorientasi Nonlaba Pada Yayasan: Studi Kasus Pada Yayasan Pendidikan Islam Al-Ikhlas Raudlatul Athfal “Al-Ikhlas” Sukabumi - Finna Julyana; Sulaeman Sulaeman; Irfan Sophan Himawan (AKUNTANSI 45, 2024)
This sudy aims to analyze the report according to ISAK 35 and find out the obstacles to making ISAK 35 financial statements at the Islamic Education Foundation Al-Ikhlas Raudlatul Athfal "Al-Ikhlas" Sukabumi. This research uses a qualitative method with a descriptive approach. Based on the research, nonprofit organizations such as foundations, their financial reporting refers to ISAK 35 related to the presentation of a nonprofit-oriented entity's financial statements with 5 (five) components of financial statements which include the statement of financial position, statement of comprehensive income, statement of changes in net assets, statement of cash flows and notes to financial statements. After analyzing what happened to this foundation in 2022, it did not use ISAK 35 financial statements as a financial reporting standard. However, the financial statements made are only simple, namely only recording cash in and cash out. As well as the initial transactions that occur are recorded first even though there is no cash to be issued so that accounting records are included in cash-based records. At the end of the year the records will be recapitulated and become a financial report that records income and expenses and is set aside as the remaining operational money or as a determinant of cash in the treasury during one period. And the obstacles to the preparation of financial statements in accordance with ISAK 35 in this foundation in terms of human resources factors.